2019
DOI: 10.1002/bse.2382
|View full text |Cite
|
Sign up to set email alerts
|

The role of environmental innovation through the technological proximity in the implementation of the sustainable development

Abstract: This paper explores the relationship between a firm's knowledge sourcing strategy and green innovation. The data are taken from Organisation for Economic Cooperation and Development REGPAT database, February 2016, relative to the European Patent Office firms' patent applications published up to December 2015.The study contributes to the literature by focusing on the moderating role of integration between different activities related to environmental performance on the relationship between knowledge sources and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…In addition, some scholars think that policy factors [17,18] and cultural factors [19,20] will also have a great impact on the social integration of reservoir-induced migrants. At the same time, environmental factors [21,22] and geopolitics [23,24] contribute to the sustainable development of migrants. Therefore, in identifying the social integration of migrants, multiple dimensions need to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some scholars think that policy factors [17,18] and cultural factors [19,20] will also have a great impact on the social integration of reservoir-induced migrants. At the same time, environmental factors [21,22] and geopolitics [23,24] contribute to the sustainable development of migrants. Therefore, in identifying the social integration of migrants, multiple dimensions need to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Since the emergence of the concept of sustainable development, social, economic, and environmental dimensions of sustainability have been considered [17][18][19], all of them with the main objective of fulfilling the necessities of people living today, but within the carrying capacity of the earth so that future generations are not damaged. The so-called social and solidarity economy addresses current challenges such as social exclusion, inequality, climate change, or unemployment.…”
Section: Sustainability and Entrepreneurshipmentioning
confidence: 99%
“…scientific and technical publications, products, and processes), it is indicated that the capability of patents to explaining most aspects of technical innovation activities has been recognized widely [40]. Basically, patent information, such as patent documents and citations, is considered as one of the sources in transferring knowledge to promote policymakers at the worldwide level, favoring promising technologies in terms of social optimum [41] and stimulate firm's strategy makers focusing from internal knowledge to external knowledge when developing product innovation [42,43]. Since the raw patent data offers detailed information on a specific invention (e.g., novel product or process) [44], previous studies suggested that patent analysis has long been employed as a useful analytical technique for TOD and has significantly benefited from the use of computerized methods such as patent statistics analysis and patent bibliometric analysis [45].…”
Section: Patent Analysismentioning
confidence: 99%